2003
DOI: 10.5551/jat.10.72
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between High-density Lipoprotein-cholesterol and Malondialdehyde-modified Low-density Lipoprotein Concentrations

Abstract: Several reports have suggested that HDL has anti-oxidative actions. We investigated the relationship between HDL-cholesterol (HDL-C) and malondialdehyde-modified LDL (MDA-LDL) concentrations using enzyme linked immunosolvent assay. We divided our study subjects into four groups on the basis of concentrations of triglyceride (TG) and HDL-C by the following lipid profiles: serum TG < or = 1.69 mmol/L and HDL-C > or = 1.16 mmol/L (control group, n = 26); TG >1.69 and HDL-C < or = 1.16 (high TG group, n = 22); TG … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 31 publications
1
15
0
Order By: Relevance
“…Furthermore, increased oxidative stress and high levels of LDL may accelerate the production of oxidized LDL. The present results suggest that pitavastatin may decrease MDA-LDL, which is known to be a form of oxidized LDL 27,28) , by two major mechanisms: a systemic oxidative stress-ameliorating effect and a LDL-C-lowering effect.…”
Section: Discussionmentioning
confidence: 81%
“…Furthermore, increased oxidative stress and high levels of LDL may accelerate the production of oxidized LDL. The present results suggest that pitavastatin may decrease MDA-LDL, which is known to be a form of oxidized LDL 27,28) , by two major mechanisms: a systemic oxidative stress-ameliorating effect and a LDL-C-lowering effect.…”
Section: Discussionmentioning
confidence: 81%
“…It has been reported that chronic treatment with AEDs was found to compete with cholesterol in the utilization of hepatic microsomal enzymes P-450 system which leads to reduction in the transformation of cholesterol in bile acids with increased serum cholesterol [24]. Hypercholesterolemia is known to result in increased endothelial permeability, retention of lipoproteins within the arterial intima, inflammatory cell recruitment and foam cell formation filled with oxidized-LDL, increase lipid peroxidation, induce vasoconstriction and enhance muscle wall proliferation and thrombotic properties [25].…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative modification of LDL may contribute to atherosclerosis by increasing its cytotoxic effects, by receptor-dependent uptake by scavengers, and by influencing the migration of monocytes effectively prevents lipid oxidation by metal ions in vitro and by cells in tissue culture 19) . In addition, it is suggested that as the HDL-cholesterol concentration falls in humans, the extent of malondialdehyde modification per LDL particle increases 20) . The HDL fraction in human plasma is in fact heterogenous.…”
Section: Introductionmentioning
confidence: 99%